Characteristics of the Gut Microbiome and IL-13/TGF-β1 Mediated Fibrosis in Post-Kasai Cholangitis of Biliary Atresia - Meng, Lingdu; Liu, Jia; Wang, Junfeng; Du, Min; Zhang, Shouhua; Huang, Yanlei; Shen, Zhen; Dong, Rui; Chen, Gong; Zheng, Shan (Frontiers in Pediatrics, 2021)
Aims: Cholangitis in biliary atresia (BA), which accelerates liver fibrosis progression, is among the most common serious complications after Kasai surgery; however, its etiology remains elusive. Gut microbiome migration may contribute to post-Kasai cholangitis. Further, there is no appropriate model of BA post-Kasai cholangitis for use in investigation of its pathogenesis. Methods: We explored the characteristics of gut microbiome in patients with BA before and after Kasai procedure based on 16S rDNA sequencing. We isolated the dominant strain from patient stool samples and established an in vitro model by infecting patient-derived liver organoids. Bulk RNA-seq was performed, and we conducted qPCR, ELISA, and western blot to explore the mechanism of fibrosis. Results: Gut microbiome diversity was lower in patients after, relative to before, Kasai procedure, while the relative abundance of Klebsiella was higher. Patients who developed cholangitis within one month after discharge tended to have simpler gut microbiome composition, dominated by Klebsiella. Klebsiella pneumoniae (KPN) was isolated and used for modelling. RNA-seq showed that BA liver organoids expressed markers of hepatic progenitor cells (KRT19, KRT7, EPCAM, etc.) and that organoids were more stable and less heterogeneous among individuals than liver tissues. After infection with KPN, gene expression patterns in BA liver organoids were enriched in pathways related to infection, apoptosis, and fibrosis. Preliminary experiment indicated the presence of IL-13/TGF-β1-mediated fibrosis in post-Kasai cholangitis. Conclusions: Our findings using a newly-developed model, demonstrate a key role for Klebsiella, and a potential mechanism underlying fibrosis in post-Kasai cholangitis, mediated by the IL-13/TGF-β1 pathway.